The Evolution of the Labor Market in the First Months of the Year (Observatorio Económico, 2015)
Even amid weak economic momentum, during the first months of 2015 the unemployment rate in Chile has remained at levels similar to those observed in the same period of the previous year (see Figure 1). Part of this stability, despite the low level of economic activity, may originate in the slowdown in labor force participation growth, particularly among women. The female participation rate even shows negative (12-month) growth rates in the two most recent quarters available for this year. Continue reading...
Keywords: Labor market; Wage employment; Job creation